2005
DOI: 10.3168/jds.s0022-0302(05)72889-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Various Antifungal Additives on the Fermentation and Aerobic Stability of Corn Silage

Abstract: In 2 consecutive years, whole plant corn was ensiled in laboratory silos to investigate the effects of various silage additives on fermentation, dry matter (DM) recovery and aerobic stability. In yr 1, chopped forage was treated with 1) no additive (untreated, U), 2) Lactobacillus buchneri 40788, 4 x 10(5) cfu/g of fresh forage (LLB4), 3) L. buchneri 11A44, 1 x 10(5) cfu/g (PLB), 4) Biomax 5 (Lactobacillus plantarum PA-28 and K-270), 1 x 10(5) cfu/g (B5), 5) Silo Guard II (sodium metabisulfite and amylase), 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
132
0
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 28 publications
18
132
0
14
Order By: Relevance
“…The WSC concentrations were higher (P < 0.05) in CH compared to C and B at days 3, 5, 10, and 90 of fermentation. As with our study, treating maize silages with the chemical-based additives has been shown to increase residual WSC concentrations, thus suggesting partial inhibition of fermentation (Kleinschmitt et al 2005;Da Silva et al 2015). The WSC which remain in silages that have undergone restricted fermentations constitute a potential source of readily available substrate for the growth of aerobic microflora when the silages are exposed to air during the feed-out period (Wilkinson and Davies 2013).…”
Section: Resultsmentioning
confidence: 84%
“…The WSC concentrations were higher (P < 0.05) in CH compared to C and B at days 3, 5, 10, and 90 of fermentation. As with our study, treating maize silages with the chemical-based additives has been shown to increase residual WSC concentrations, thus suggesting partial inhibition of fermentation (Kleinschmitt et al 2005;Da Silva et al 2015). The WSC which remain in silages that have undergone restricted fermentations constitute a potential source of readily available substrate for the growth of aerobic microflora when the silages are exposed to air during the feed-out period (Wilkinson and Davies 2013).…”
Section: Resultsmentioning
confidence: 84%
“…The aerobic stability was improved in all treated silages due to the low number of yeast in these silages, as reported by Muck (2010) when L. buchneri was used. Driehuis et al (1999), Ranjit & Kung Jr. (2000), Nishino et al (2003) and Kleinschmit et al (2005) reported an improvement in the aerobic stability cof corn silage inoculated with ≥1×10 6 cfu of L. buchneri 40778/g. Ranjit et al (2002) found improved aerobic stability in corn silage inoculated with 1×10 5 , 2.5×10 5 , 5×10 5 or 1×10 6 cfu of L. buchneri 40778/g, but in silages with higher doses (5×10 5 and 1×10 6 cfu/g), the temperature did not increase for 572 hours.…”
Section: Resultsmentioning
confidence: 99%
“…A inoculação das silagens com a combinação das BAL promoveu acréscimo na concentração do ácido acético, o que está de acordo com os resultados observados por outros pesquisadores que utilizaram BAL heterofermentativas e homofermentativas associadas (Filya, 2003;Filya et al, 2006;Kleinschmit et al, 2005). Isto ocorre devido ao L. buchneri converter hexoses em ácido lático, ácido acético, CO 2 e água (McDonald et al, 1991).…”
Section: Resultsunclassified